Evaluation and selection of rice mutants for high yield and quality fodder production - Abisola, Oladosu Yusuff (2014)
Increasing genetic variability with mutagenic agents has been broadly employed in plant breeding because this method alters one or more desirable traits, creating an effective breeding programme. Based on this background, this study was performed to evaluate the genetic diversity of derived mutant lines and to establish the relation between yield and its components in them using multivariate analysis to select the best genotype in grain yield and high nutritional quality. To achieve this objective, two field trials were performed on 45 rice genotypes and four Malaysian commercial varieties to evaluate their growth and yield traits, and to perform a comparative nutrient analysis. From data collected on quantitative traits, analysis of variance, variance components, heritability, genotypic and phenotypic coefficient variation, and expected genetic advance were estimated. All the vegetative and yield traits showed significant variations among the genotypes. Additionally, all of the traits correlated positively with the final yield, except for number of tillers. To complement this study, molecular methods were used to study to further confirm the outcome of this research, establishing the relation between the two methods. The genetic diversity of the 45 genotypes was analysed using 25 inter-simple sequence repeats markers (ISSRs). The data were analysed using NT-SYS software to estimate the genetic relations among the rice accession from different sources, i.e., Malaysia, Bangladesh and Vietnam, to detect level of polymorphism within and between populations. The analysis of the molecular variance showed that 90% of total genetic variations were due to differences within populations, whereas 10% of total genetic variations were due to differences among populations. A positive correlation was observed between similarity distance between the morphological traits and the ISSR molecular data. Both methods, morphological traits and molecular markers are useful tools for assessing the genetic variability and diversity of the mutant rice genotypes. Data on fodder quality, namely, proximate composition of cell wall content analyses, primary and trace mineral components varied significantly among the genotypes for all of the traits except acid detergent fibre (ADF), acid detergent lignin (ADL), organic matter digestibility (OMD), metabolisable energy (ME), cellulose and hemicellulose. The results from this study indicated that ion beam radiation caused significant changes in the agronomic performance of majority of the mutant lines compared with the parental variety (MR219), based on genetic diversity results and agronomic traits performance. Evaluation over two locations, mutant lines ML21, ML10, ML4, ML6 and ML9 performed better in terms of yield production compared to other mutants. The result from the nutritional characteristic assessment revealed that ML24 and ML22 rice straw was better in CP, N, P, Mg content compared with other genotypes.